2019
DOI: 10.3390/cells8111395
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Enhances the Invasiveness of Hepatocellular Carcinoma via EGFR-Mediated Invadopodia Formation and Activation

Abstract: Hepatocellular carcinoma (HCC) represents the fifth most common cancer worldwide and the third cause of cancer-related mortality. Hepatitis C virus (HCV) is the leading cause of chronic hepatitis, which often results in liver fibrosis, cirrhosis, and eventually HCC. HCV is the most common risk factor for HCC in western countries and leads to a more aggressive and invasive disease with poorer patient survival rates. However, the mechanism by which the virus induces the metastatic spread of HCC tumor cells throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…EGF expression is a main driver of liver fibrosis and HCC [61] and is part of a prognostic transcriptional signature associating with HCC development and patient survival [62][63][64]. Moreover, a recent study has shown that HCV infection induces the EGFR-dependent expression of invadopodia-related genes, therefore enhancing intra-and extrahepatic HCC dissemination in vivo [65].…”
Section: Egf Signaling Pathwaymentioning
confidence: 99%
“…EGF expression is a main driver of liver fibrosis and HCC [61] and is part of a prognostic transcriptional signature associating with HCC development and patient survival [62][63][64]. Moreover, a recent study has shown that HCV infection induces the EGFR-dependent expression of invadopodia-related genes, therefore enhancing intra-and extrahepatic HCC dissemination in vivo [65].…”
Section: Egf Signaling Pathwaymentioning
confidence: 99%
“…First, previous reports demonstrated the activation of EGFR by HCV proteins [ 70 , 71 , 72 , 73 , 74 , 75 ]. We have recently demonstrated that HCV infection constitutively activates EGFR thus inducing invasion of HCV-infected cells [ 76 ]. Moreover, among the pathways that we have identified to be epigenetically altered, the top pathway was cytoskeleton remodeling, which is known to be induced by EGFR signaling [ 7 ].…”
Section: Possible Mechanisms Of Epigenetic Imprinting By Hcv Infecmentioning
confidence: 99%
“…The majority of differentially expressed genes, as assessed by transcriptomic analysis, were not altered after eradication of the virus, suggesting a potential link between HCV-imprinted gene expression and epigenetic changes underlying HCV-related hepatocarcinogenesis. Gal-Tanamy et al performed integrated transcriptome, epigenome, and kinome screens and determined that activation of epidermal growth factor receptor (EGFR) following HCV infection upregulates the expression of invasion-related genes [3]. Regarding their results, HCV NS3 protease cleaves and inactivates T-cell protein tyrosine phosphatase (TCPTP), a phosphatase that inhibits EGFR signaling, contributing to HCV-induced invasion phenotypes.…”
Section: Hepatocellular Carcinoma Cirrhosis and Pathogenesismentioning
confidence: 99%